1993
DOI: 10.1073/pnas.90.15.7158
|View full text |Cite
|
Sign up to set email alerts
|

Binding to heparan sulfate or heparin enhances neutrophil responses to interleukin 8.

Abstract: The interaction of interleukin 8 (IL-8) with heparin was studied by using synthetic IL-8 analogs with Cand N-terminal truncations. Elimination of the N-terminal region preceding the first cysteine, which constitutes the IL-8 receptor binding site, did not affect the afnity to heparinSepharose. Affinity, however, decreased with progressive truncation at the C terminus, and no binding was observed when the C-terminal a-helix was eliminated. The effect of heparin and other glycosaminoglycans on IL-8 activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
285
2
3

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(298 citation statements)
references
References 46 publications
8
285
2
3
Order By: Relevance
“…This view has been challenged by studies showing that the formation of complexes with the GAG side chains of proteoglycans is generally needed for the in vivo activity of certain chemokines. Previously, it was found that IL-8 must bind GAG to elicit directed neutrophil migration (52). More recently, Li et al (53) could demonstrate that the release of complexes between the cell surface proteoglycan syndecan-1 and the chemokine KC from the epithelium in lung injury is regulated by the matrix metalloproteinase matrilysin (MMP-7).…”
Section: Discussionmentioning
confidence: 99%
“…This view has been challenged by studies showing that the formation of complexes with the GAG side chains of proteoglycans is generally needed for the in vivo activity of certain chemokines. Previously, it was found that IL-8 must bind GAG to elicit directed neutrophil migration (52). More recently, Li et al (53) could demonstrate that the release of complexes between the cell surface proteoglycan syndecan-1 and the chemokine KC from the epithelium in lung injury is regulated by the matrix metalloproteinase matrilysin (MMP-7).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes are able to sense several distinct chemokine gradients, hence sustaining directed migration (Foxman et al, 1997). Endothelial cells contain a thick glycocalyx rich in proteoglycans, which serve as anchoring structures for chemokines (Tanaka et al, 1993;Webb et al, 1993). By this mechanism, retention of these molecules at the endothelial surface and presentation to leukocytes can be achieved.…”
Section: Molecular Mechanisms That Control Leukocyte Extravasationmentioning
confidence: 99%
“…Consequently, the discovery that chemokines are bound by cell surface GAG gave rise to the theory that haptotactic, or cell-bound, concentration gradients provide vectorial information in vivo. 5,47 A variety of experiments have shown that GAG are critically important for chemokine activity, 3,5,23,48 with loss of cell surface heparan sulfate severely limiting chemokine activity. 34,42,49 Soluble chemokine concentration gradients have been shown to direct immune cell migration in vitro.…”
Section: Competition Of Cell Surface Mcp-1 Binding By Heparinmentioning
confidence: 99%
“…2 Interaction with a low-affinity receptor, the cell surface glycosaminoglycans (GAG), is usually mediated via the C-terminus of the protein and often via a specific BBXB motif. 3,4 Chemokines display a range of affinities for the various glycosaminoglycan components of cell surface and extracellular proteoglycans, predominantly binding to the highly sulfated heparin-like species, heparan sulfate. 5 The ability to discriminate between different GAG molecules is believed to reside in paired glutamic acid residues within putative GAG-binding sites.…”
mentioning
confidence: 99%